Right to equality and non-discrimination of public servants with disabilities and provisional appointment - Alemán Guerrero , Bryan Patricio (2025)
This study analyzes the violation of the right to equality and non-discrimination of public servants with disabilities under provisional appointment in Ecuador. The objective was to examine this issue to propose a framework of measures that guarantees their job stability and the effective implementation of reasonable adjustments. The research adopted a mixed methodology with a non-experimental cross-sectional design. Techniques such as a survey of 27 public servants and interviews with experts in constitutional law were applied. The re-sults reveal that the majority (85%) experience administrative changes that do not consider their disability, lack physical accessibility (91%), and perceive a clear violation of the princi-ple of equality (100%). It is concluded that structural discrimination exists, proposing a com-prehensive intervention with normative reforms in the LOSEP, protocols, and training to ma-terialize substantive equality in public administration, ensuring stable working conditions adjusted to the needs of this group in a situation of double vulnerability.